Memorial Park – Port-of-Spain - Khan, Farouk (Print Master Limited, Trinidad, 2010)
Six wooden and concrete benches, face one another, as they flank one of the four pathways leading up to the cenotaph, installed here on 28 June 1924, in the centre of the War Memorial Park, often referred to as “Memorial Park”. The benches seem to welcome you to sit and remember the Trinidad and Tobago nationals who served and died in World Wars I and II, 1914-1918 and 1939-1945. A man and a woman are seated on one of the benches, in the foreground. In the distant background are the Laventille Hills.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Monuments--Trinidad and Tobago; Memorials--Trinidad and Tobago; Statues--Trinidad and Tobago; Benches--Trinidad and Tobago; Buildings--Trinidad and Tobago; Parks--Trinidad and Tobago; World War, 1914-1918--Monuments--Trinidad and Tobago; World War, 1939-1945--Monuments--Trinidad and Tobago; War Memorial Park (Port of Spain)